Quit behavior and the role of job protection - Anne C. Gielen; Konstantinos Tatsiramos (Institute for the Study of Labor (IZA), 2012)
Job protection reduces job turnover by changing firms' hiring and firing decisions. Yet the effect of job protection on workers' quit decisions and post-quit outcomes is still unknown. We present the first evidence using individual panel data from 12 European countries, which differ both in worker turnover rates and in the level of job protection. We find that workers are less likely to quit their job in countries with more job protection, but conditional on quitting they receive higher wages. This evidence can be explained by increased mobility costs associated with higher expected risk of post-quit layoff and job mismatch.
Keywords: J28; J62; 330; institutions; employment protection; labor mobility; job satisfaction; wages; Arbeitnehmerschutz; Arbeitsmobilität; Kündigung; Arbeitszufriedenheit; Lohn; Schätzung; Europa